2018
DOI: 10.3892/ijmm.2018.3551
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-130a regulates chondrocyte proliferation and alleviates osteoarthritis through PTEN/PI3K/Akt signaling pathway

Abstract: The function of microRNA‑130a in development and progression of osteoarthritis was determined. In osteoarthritis patients, the serum levels of microRNA‑130a were decreased, compared with normal group. Overexpression of microRNA‑130a increased cell proliferation and decreased apoptosis of chondrocytes, and downregulation of microRNA‑130a also decreased cell proliferation and induced apoptosis in chondrocytes. Downregulation of microRNA‑130a promoted Bax and caspase‑3/9 protein expression, increased inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…To clarify the downstream mechanism of miR‐26a‐5p after its entry into SW1353 cells, the target genes of miR‐26a‐5p were predicted through a database and 49 genes were obtained in the intersection (Figure 5A). Among them, PTEN was reported to be high‐expressed in OA 25,26 . Based on the binding site between miR‐26a‐5p and PTEN, a dual‐luciferase reporter gene assay was performed (Figure 5B), which confirmed the target binding relationship between miR‐26a‐5p and PTEN ( p < 0.01) (Figure 5C).…”
Section: Resultsmentioning
confidence: 70%
“…To clarify the downstream mechanism of miR‐26a‐5p after its entry into SW1353 cells, the target genes of miR‐26a‐5p were predicted through a database and 49 genes were obtained in the intersection (Figure 5A). Among them, PTEN was reported to be high‐expressed in OA 25,26 . Based on the binding site between miR‐26a‐5p and PTEN, a dual‐luciferase reporter gene assay was performed (Figure 5B), which confirmed the target binding relationship between miR‐26a‐5p and PTEN ( p < 0.01) (Figure 5C).…”
Section: Resultsmentioning
confidence: 70%
“…Zeng et al (2019) showed that high expression of MMP3 was observed in OA synovial cells, and curcumin could control cell proliferation and induce cell apoptosis by inhibiting MMP3 expression, eventually alleviating OA inflammation. AKT, a serine/threonine protein kinase, is an effector of the PI3K/AKT signaling pathway (Malemud, 2015) and is involved in multiple biological processes, including cell growth, apoptosis, migration, and metabolism (Zhang et al, 2018). PTEN is an important negative regulator of the PI3K/AKT signaling pathway, and loss of PTEN can lead to the activation of the PI3K/AKT signaling pathway (Xi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…PTEN is an important negative regulator of the PI3K/AKT signaling pathway, and loss of PTEN can lead to the activation of the PI3K/AKT signaling pathway (Xi et al, 2020). A study by Zhang et al (2018) indicated that miRNA-130a could regulate cell growth and relieve OA via the PTEN/PI3K/AKT signaling pathway. Additionally, GRPR is a member of the G-protein coupled receptor superfamily and affects cell growth and invasion (Elshafae et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that miRNAs are key endogenous regulators of stem cell differentiation [3, 69]. Use of miRNA mimics is an excellent strategy to enhance osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), which contain 20–30 nucleotides, regulate endogenous gene expression by inhibiting posttranscriptional gene expression or inducing degradation of their targets via binding to the 3′ untranslated regions of messenger RNAs (mRNAs) [15]. Accumulated evidence suggests that many miRNAs help to regulate osteogenic differentiation of bone mesenchymal stem cells (BMSCs) [3, 69]. MiR-29b, one of the most widely investigated miRNAs, regulates osteogenic differentiation via several mechanisms.…”
Section: Introductionmentioning
confidence: 99%